THE SYNTHESIS OF 1-DECYL-3-METHYLIMIDAZOLIUM BROMIDE IONIC LIQUID UTILIZING MICROWAVE ASSISTED ORGANIC SYNTHESIS (MAOS) METHOD AS A MEDIUM IN MICROCRYSTALLINE CELLULOSE CONVERSION - Yuliana Dwi Cahya, Angelina
Exploration of fossil fuels on a large scale from day to day can cause their availability to run out and trigger global warming. One alternative to reduce the use of fossil fuels is to process biomass materials into bioenergy products in the one-pot reaction process. There are several bioenergy-producing compounds, including formic acid, levulinic acid, and 5-hydroxymethylfurfural. The development of bioenergy in Indonesia is quite potential because it has a tropical climate, which have abundantly biological natural resources, especially in producing biomass. The results of previous studies show that the conversion of biomass into bioenergy products generally uses metal-based catalysts. As is well known, transition metalbased catalysts are expensive, difficult to recycle, and are toxic to humans. Therefore, mediators are needed to minimize environmental pollution also can be reused with high effectiveness and efficiency. Ionic liquids known as organic salt compounds, which act not only as solvents but also as mediator in biomass conversion. This research will examine the conversion of microcrystalline cellulose using imidazolium-based ionic liquid as a reaction mediator and solvent. The general series of this research are to synthesize 1-decyl-3-methylimidazolium bromide ([DMIM]Br) using MAOS, then to apply the [DMIM]Br in converting microcrystalline cellulose. The ionic liquid [DMIM]Br was obtained with high yields up to 73%. It has been successfully synthesized with relatively short reaction time of 30 seconds at 800 Watt. The result of FT-IR spectroscopy showed a wave number of 700 cm-1 is related with the absorption of the quaternary (-CH2-) group in alkyl chain. The 1H NMR spectrum was performed a typical triplet proton signal at 4.18-4.29 ppm originating from the quaternary –CH2 group, while the 13C NMR measurement was performed that the number of C atoms have similar to the number C atoms in [DMIM]Br. The [DMIM]Br is used as a mediator as well as a solvent in the conversion of microcrystalline cellulose. The conversion reaction uses an oven within 2 hours and the reaction temperature is in the range of 130 – 170 oC. As for the treatment of the reaction system, using a sulfuric acid catalyst solution, which use a concentration of 0.2 M and 1 M respectively. In addition, the reaction was also carried out without using a sulfuric acid catalyst. The GC-MS (Gas Chromatography Mass Spectrometry) instrument was used to identify compounds from the conversion of microcrystalline cellulose in the methyl isobutyl ketone (MIBK) solution phase. The 5-hydroxymethylfurfural compound with an optimum percent composition of 15.73% took place at 130 oC using [DMIM]Br and without sulfuric acid solution as catalyst. Conversion of microcrystalline cellulose in 1 M sulfuric acid solution can produce formic acid with an optimum percent composition of 35.29% at 140 oC. Levulinic acid with optimum percent composition of 77.14% was successfully produced at 150 oC using 1 M of sulfuric acid solution. Recycling studies were carried out on the liquid phase using dichloromethane solvent, especially for the convertion with sulfuric acid catalyst solution. In addition, the vacuum distillation method is used to recycle the liquid phase for the convertion without the sulfuric acid catalys. The results of one recycling process, obtained an average percentage of [DMIM]Br of 53%. Recycling studies showed that the [DMIM]Br ionic liquid has the potential to be reused to convert microcrystalline cellulose to produce formic acid, levulinic acid, acetic acid, 2,3-anhydro-D-galactosan, dihydro-4,4,5,5-tetramethyl-efisienfuranone and 5-hydroxymethylfurfural.